Oxidized low density lipoprotein in the liver causes decreased permeability of liver lymphatic- but not liver sinusoidal-endothelial cells via VEGFR-3 regulation of VE-Cadherin - Goldberg, Alyssa R.; Ferguson, Megan; Pal, Sarit; Cohen, Rachel; Orlicky, David J.; McCullough, Rebecca L.; Rutkowski, Joseph M.; Burchill, Matthew A.; Tamburini, Beth A. Jirón (Frontiers in Physiology, 2022)
The lymphatic vasculature of the liver is vital for liver function as it maintains fluid and protein homeostasis and is important for immune cell transport to the lymph node. Chronic liver disease is associated with increased expression of inflammatory mediators including oxidized low-density lipoprotein (oxLDL). Intrahepatic levels of oxLDL are elevated in nonalcoholic fatty liver disease (NAFLD), chronic hepatitis C infection (HCV), alcohol-associated liver disease (ALD), and cholestatic liver diseases. To determine if liver lymphatic function is impaired in chronic liver diseases in which increased oxLDL has been documented, we measured liver lymphatic function in murine models of NAFLD, ALD and primary sclerosing cholangitis (PSC). We found that Mdr2-/- (PSC), Lieber-DeCarli ethanol fed (ALD) and high fat and high cholesterol diet fed (NAFLD) mice all had a significant impairment in the ability to traffic FITC labeled dextran from the liver parenchyma to the liver draining lymph nodes. Utilizing an in vitro permeability assay, we found that oxLDL decreased the permeability of lymphatic endothelial cells (LEC)s, but not liver sinusoidal endothelial cells (LSEC)s. Here we demonstrate that LECs and LSECs differentially regulate SRC-family kinases, MAPK kinase and VE-Cadherin in response to oxLDL. Furthermore, Vascular Endothelial Growth Factor (VEGF)C or D (VEGFR-3 ligands) appear to regulate VE-Cadherin expression as well as decrease cellular permeability of LECs in vitro and in vivo after oxLDL treatment. These findings suggest that oxLDL acts to impede protein transport through the lymphatics through tightening of the cell-cell junctions. Importantly, engagement of VEGFR-3 by its ligands prevents VE-Cadherin upregulation and improves lymphatic permeability. These studies provide a potential therapeutic target to restore liver lymphatic function and improve liver function.